MENYOAL KESENJANGAN ANTARA DAS SEIN DAN DAS SOLLEN PENYEBARAN ISLAM PRA WALISONGO - Widiastuti, Widiastuti (Jurnal Ilmu Dakwah, 2017)
This Artikel based on historical research. The result of research was indicated thats Islam has been spread in Java since the 7th century, and has even successfully Islamized two Javanese priyayi namely Rakeyan Sancang from Tarumanegara and Prince Jay Shima from Kalingga. However, the reality of data on the development of the number of Javanese Muslim communities from the 7th-14th century AD was minimal. This fact tell about the passive indigenous Muslims. While in the Walisongo (14-16 AD), in a relatively short span of time was able to change the number of Muslim minorities into the majority. Thus, in the history of pre-walisongo Islam spread the imbalance between hope and reality arises. The spread of pre-walisongo Islam has taken a very long time, so the expectation is to produce significant quantity and quality development of Muslim societies. But the fact that it did not materialize because the spread of Islam is less successful both in quantity and quality.